The Thought of Wahbah Al-Zuhayli in Al-Munir Fi Al-Aqidah Wa Al-Syari'ah Al-Manhaj [Pemikiran Tafsir al-Munir fi al-Aqidah wa al-Syari’ah al-Manhaj karya Dr. Wahbah al-Zuhayli] - Sulfanwandi Sulfanwandi (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2021)
Abstract: Alquran is a for mankind in which there are several aspects such as aspects of balaghah, ma'ani, and other Arabic literature. Therefore, it is necessary to have an interpretation that acts as an explanation of the meaning of the verses of Alquran. In the treasury of interpretation, there have been many commentators who have interpreted Alquran from classical to contemporary crosses. The commentators examine the verses of Alquran with various styles and characteristics of each. In this case, the author sees the uniqueness of Wahbah al-Zuhayli in interpreting Alquran and he is a contemporary scholar who links interpretation and sharia. Then it can be seen how he interprets Alquran and what are the advantages and disadvantages of the book of interpretation. Abstrak: Al-Quran merupakan petunjuk dan pedoman bagi umat manusia yang di dalamnya terdapat beberapa aspek seperti aspek balaghah, ma’ani, dan sastra Arab lainnya. Oleh karena itu, perlu adanya tafsir yang berperan sebagai penjelas terhadap makna ayat-ayat Alquran. Di dalam khazanah tafsir sudah banyak mufassir yang menafsirkan Alquran dari lintas klasik hingga kontemporer. Para mufassir menelaah ayat-ayat Alquran dengan corak-corak beragam dan ciri khas masing-masing. Dalam hal ini penulis melihat adanya keunikan dari Wahbah al-Zuhayli dalam menafsirkan Alquran dan beliau merupakan ulama kontemporer yang mengaitkan tafsir dan syariah. Maka dapat dilihat bagaimana cara beliau dalam menafsirkan Alquran serta apa kelebihan dan kekurangan dari kitab tafsir tersebut.